Energy Statistics Yearbook 2020 - United Nations Department of Economic; Social Affairs (United Nations, 2023)
The 2020 Energy Statistics Yearbook is the sixty-fourth issue in a series of annual compilations of internationally comparable statistics summarizing world energy trends. Annual data for 225 countries and areas for the period 2017 to 2020 are presented on production, trade and consumption of energy: solids, liquids, gaseous fuels, electricity and heat, covering both renewable and non-renewable sources of energy. In addition, per capita consumption series are also provided for all energy products. Graphs are included to illustrate historic trends and/or changes in composition of production and/or consumption of major energy products. Special tables of interest include: international trade tables for coal, crude petroleum and natural gas by partner countries – providing information on direction of trade; selected series of statistics on renewables and wastes; refinery distillation capacity; and a table on selected energy resources.